Venezuela: Political Confrontation and the World Community - Z. W. Iwanowski; D. M. Rozental (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The paper examines a complex web of domestic and external issues which have both provoked a systemic crisis in Venezuela and, at the same time, determined its speciﬁcity in comparison with the wave of protests sweeping across Latin America in 2019.The authors conclude that the escalation of the conﬂict in Venezuela was caused not only by the standoﬀ between the legislative and the executive branches of the government, but also by the split of the whole society into proponents and opponents of ‘socialism of the 21st century’. The contradictions have led to the formation of the parallel branches of power: two presidents, two parliaments and two supreme courts (one of them in exile) which de facto coexist in the country and each claims exclusive rights and legitimacy.The authors also stress that the situation in Venezuela has obvious regional consequences. The miscalculations of the incumbent president were used in election campaigns in other Latin American countries and became one of the reasons for the defeat of left candidates, the subsequent ‘right drift’ leading to the isolation of the republic. The new political landscape has also aﬀected the architecture of integration associations, which failed to develop a uniﬁed position toward the Bolivarian regime.Furthermore, in a current heightened state of international tensions Venezuela has turned into a theatre of international rivalry and conﬂict involving all the key subjects of world politics. The United States, China, Russia and the European Union compete for the energy resources of the country and pursue their own strategic interests. The inability or unwillingness of external forces to reach compromise and to bring the parties to the negotiating table can pose a threat to peace and international security.As a result, Venezuela has become one of the most turbulent countries in the region. At the same time, the repeated outbursts of protest waves are signiﬁcantly diﬀerent from popular uprisings in other Latin American states. In the worst-case scenario, a constantly worsening situation may result in a social explosion which threatens to make the Bolivarian Republic another hot spot of the planet.